Synchrotron X-ray assisted degradation of industrial wastewater by advanced oxidation process. (August 2022) - Jadhav, A.P.; Phatangare, A.B.; Ganesapandy, T.S.; Bholane, G.T.; Sonawane, A.M.; Khantwal, N.; Kamble, P.N.; Mondal, P.; Dhamgaye, V.P.; Dahiwale, S.S.; Phase, D.M.; Bhoraskar, V.N.; et al.
Abstract: Various methods for the degradation and detoxification of textile effluents have been developed in recent years and among these, advanced oxidation processes (AOPs) have been proven to be a successful way of degrading organically contaminated water into a useful form. The synchrotron X-ray (3–20 keV) irradiation-assisted AOP has been developed for the degradation of single and mixed colored industrial wastewater solution. Irradiation experiments were conducted on industrial effluents obtained straight from the cloth industries. The efficiency of AOP was measured by characterizing irradiated industrial wastewater solutions with optical, chemical, and biological characterization techniques. The UV-Vis spectroscopy and chemical oxidation demand (COD) results revealed that the wastewater was degraded and the degradation efficiency could be tailored by varying the X-ray dose. The complete decolorization and ∼ 85% removal in COD was obtained at the X-ray dose of 15000 mAs. Chemical species present in pristine and irradiated wastewater were analyzed using FTIR techniques. The FTIR spectra revealed the destruction of the aromatic ring and nitrogen linkage of wastewater under X-ray irradiation. The technique of liquid chromatography-mass spectroscopy (LC-MS) was employed to identify and quantify the unknown compounds present in pristine as well as X-ray irradiated wastewater solutions. Toxicity assays on gram-negative Escherichia coli (DH5α) clearly show detoxification of X-ray irradiated solutions. This study demonstrates a fast and effective approach for completely degrading and detoxifying industrial wastewater, and has a wide range of applications in environmental remediation. Highlights: Synchrotron X-ray-assisted degradation of industrial wastewater was investigated. Efficiency of AOP was assessed based on degradation, COD & toxicity of wastewater. Synchrotron X-rays reduced 85% COD and 99% coloration of wastewater solutions. Inhibition growth of E-Coli shows detoxification of wastewater after irradiation. Synchrotron X-ray irradiation based AOP could be used for pollutant degradation.